Effectiveness of a novel propylene glycol protocol in reducing ketosis in transition dairy cows - Song, Yuxi; Jiang, Xuejie; Hao, Yu; Sun, Rui; Bai, Yunlong; Shao, Guang; Ren, Wanxia; Xia, Cheng (Frontiers in Veterinary Science, 2025)
Ketosis is a prevalent metabolic disease in dairy cows, characterized by adverse effects on both animal health and production performance. Propylene glycol (PG), recognized for its glucogenic properties, is widely utilized in the therapeutic management of ketosis. This study evaluated the efficacy of two PG-based treatment protocols in mitigating ketosis and enhancing the metabolic health of Holstein cows. Ninety cows were randomly allocated into three groups (n = 30 each): control (Group C, no PG), original PG protocol (Group O, 500 mL PG orally drenched once daily on days 0, 1, 2, 7, 8, and 9 post-calving), and novel PG protocol (Group N, 500 mL PG orally drenched once daily on days 0, 7, and 14 post-calving). Data were collected for body condition score, milk yield, metabolic biomarkers, and the incidence of ketosis from 14 (±3) days prepartum to 50 days postpartum. The results demonstrated that the novel PG protocol, compared with the control group, significantly enhanced energy metabolism by modulating glucose, insulin, and leptin levels while reducing β-hydroxybutyric acid and non-esterified fatty acid concentrations (p < 0.05). Additionally, the novel PG protocol effectively decreased the incidence of ketosis (from 33.3% in Group C to 6.7% in Group N at 14 days postpartum), alleviated liver injury, and mitigated oxidative stress in dairy cows (p < 0.05). These findings underscore the potential of the novel PG protocol to improve metabolic health and reduce the risk of ketosis during the critical transition period in dairy cows. This offers a promising strategy for managing this condition in modern dairy production systems.